A Review on Mangrove Actinobacterial Diversity: The Roles of Streptomyces and Novel Species Discovery - Jodi Woan-Fei Law; Priyia Pusparajah; Nurul-Syakima Ab Mutalib; Sunny Hei Wong; Bey-Hing Goh; Learn-Han Lee (Progress in Microbes and Molecular Biology)
In the class Actinobacteria, the renowned genus Streptomyces comprised of a group of uniquely complex bacteria that capable of synthesizing a great variety of bioactive metabolites. Streptomycetes are noted to possess several special qualities such as multicellular life cycle and large linearized chromosomes. The significant contribution of Streptomyces in microbial drug discovery as witnessed through the discovery of many important antibiotic drugs has undeniably encourage the exploration of these bacteria from different environments, especially the mangrove environments. This review emphasizes on the genus Streptomyces and reports on the diversity of actinobacterial population from mangroves at different regions of the world as well as discovery of mangrove-derived novel Streptomyces species. Overall, the research on diversity of Actinobacteria in the mangrove environments remains limited. A total of 19 novel Streptomyces spp. isolated from mangroves between the year 2009 - early 2019, notably from China, India, Malaysia, and Thailand. Hence, it will be worthwhile to encourage the study of these bacteria from mangroves of different locations.